Development Of Silica-Based And Activated Carbon-Based Catalysts For Glycerol Acetylation, Transesterification And Acetalization Processes For The Production Of Oxygenated Fuel Additives - Khayoon, Muataz Shakir (2013)
The escalating growth of biodiesel industry worldwide has led to generate an abundance of glycerol, which affects the biodiesel economy. Thus, this research emphasized on the conversion of glycerol to valuable chemicals "oxygenated fuel additives". Glycerol was separately transformed to diversified components (glycerol acetates, glycerol acetals, and glycerol carbonate) via four different catalytic reaction processes (acetylation with acetic acid, transesterification with methyl acetate, acetalization with acetone, and transesterification with dimethyl carbonate). To achieve these goals, different heterogeneous catalysts were synthesized to facilitate the production of the aforementioned components. As such, sulphated activated carbon, β-MoO3 functionalized hybrid SBA-15, and Yttrium grafted SBA-3 catalysts were synthesized and accordingly employed for the acetylation of glycerol with acetic acid. The synthesized catalysts were characterized to study their textural properties, nature of their functional groups, and their surface morphology by BET, FTIR, XRD, SAXS, 31P MAS NMR, surface acidity and basicity, CHNS/O, EDX, SEM and TEM. Mono-, di- and triacetyl glycerol (MAG, DAG and TAG, respectively) were the products of acetylation reaction and transesterification reaction with methyl acetate. Five and six membered ring acetals were the acetalization reaction products, and the valuable glycerol carbonate was the product of glycerol transesterification with dimethyl carbonate.